Experimentally quantifying anion polarizability at the air/water interface - Yujin Tong (Nature Portfolio, 2018)
Understanding anion-specific interactions with hydrophobic interfaces is challenging due to an absence of local structural probes. Here, the authors experimentally quantify the anisotropy of perchlorate’s polarizability at the air/water interface, a window into anion and solvation shell structure.